Anti-Inflammatory, Analgesic Activities, and Phytochemical Study of Traganum nudatum Delile: Biological effect and composition of Traganum nudatum Delile - Benhassine, Ikram; Ouafi, Saida; Eras, Jordi; Harrat, Zoubir; Bouslama, Zihad; Canela-Garayoa, Ramon (Iranian Journal of Pharmaceutical Sciences, 2021)
Traganum nudatum Delile is a North African endemic medicinal plant commonly used in traditional medicine to treat wounds, hemorrhoids, rheumatism, and ear infections. Nevertheless, there are no scientific reports on the anti-inflammatory and analgesic effects of this plant. The present study aims to assess the therapeutic effect of the aqueous extract of the aerial part of the plant at three doses (40, 80, and 120 mg/kg) on experimentally pain-induced animals. First, the anti-inflammatory activity was assessed by carrageenan-induced paw edema on Swiss albino mice. Secondly, the analgesic activity was assessed by the acetic acid-induced writhing test. In addition, UPLC-MS-PDA and GC-MS-FID analyses were performed to screen the possible therapeutic compounds. The anti-inflammatory effect of the aqueous extract at 120 mg/kg for 4 h experiment was significantly higher (89.97± 0.17%) than those of the reference drug acetylsalicylic acid (ASA) (0± 0.25%);. In comparison, the analgesic test showed a remarkable reducing pain effect (69.8 ± 1.7%) at the dose of 80 mg/kg, almost similar to those of Acetaminophen (Paracetamol) (72.54 ± 2.26 %). The phytochemical screening revealed the presence of therapeutic biomolecules such as flavonoids, mainly rutin (6440± 3.0 μg/g), flavonols (narcissoside 115.1± 1.4 μg/g) and phenolic acids (chlorogenic acid 1480± 1.6 μg/g). GC-MS-FID showed the presence of saturated acids such as behenic and palmitic acid with percentages of 35.58 ± 0.06 % and 17.54 ± 0.09 %, respectively. These were in a higher percentage than the unsaturated fatty acids. These results validated the use of T.nudatum Delile for treating inflammatory and analgesic disorders in folk medicine. The presence of bioactive compounds, including polyphenols and fatty acids, may explain the pharmacological effect of the medicinal plant.